PENGARUH BUDAYA KERJA, MOTIVASI KERJA DAN BEBAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN SERDANG BEDAGAI - L, Melias Metami; Surya, Aldwin; Sembiring, Rasmulia (LPPM Universitas Darma Agung, 2020)
This study aims to determine the effect of work culture, work motivation and work load on employee work productivity at the Regional Civil Service Agency of Serdang Bedagai Regency. This research is a correlational statistical study, where the data obtained is disclosed based on data in the field. The data is then analyzed by statistical methods. The data collected includes three independent variables, namely work culture (X1), work motivation (X2), and workload (X3) as well as one dependent variable, namely work productivity (Y). This research was conducted at the Regional Civil Service Agency (BKD) Serdang Bedagai Regency office. The research began to be carried out on December 2019 to March 2020. Sampling technique is used to determine the sample to be used in the research, so that an estimated value can be obtained. The sampling technique in this study is the saturated sampling method so that the number of samples in this study is 40 respondents. Data analysis was done by using multiple linear regression analysis. The results show that work culture partially has a significant effect on employee work productivity at the Regional Civil Service Agency of Serdang Bedagai Regency with a t-count value of 5.069> from t-table 1.685 or with a significance value of 0.000 < 0.05. Work motivation partially has a significant effect on work productivity at the Regional Civil Service Agency of Serdang Bedagai Regency with a t-count value of 2.248> from the t-table 1.685 or with a significance value of 0.031 < 0.05. Work load partially has a significant effect on work productivity at the Regional Civil Service Agency of Serdang Bedagai Regency with a t-count value of 2.643 > from the t-table 1.685 or with a significance value of 0.012 < 0.05. Work culture, work motivation and workload simultaneously have a significant effect on the workload of the Serdang Bedagai District Civil Service Agency with an F-count value of 36.934 > F-table 2.87 or with a significance value of 0.000 < 0.05.